2000
DOI: 10.1001/archinte.160.6.786
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Causes, and Outcome of Delirium in Patients With Advanced Cancer

Abstract: Delirium is a frequent, multifactorial complication in advanced cancer. Despite its terminal presentation in most patients, delirium is reversible in approximately 50% of episodes. Delirium precipitated by opioids and other psychoactive medications and dehydration is frequently reversible with change of opioid or dose reduction, discontinuation of unnecessary psychoactive medication, or hydration, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
207
4
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 671 publications
(223 citation statements)
references
References 45 publications
4
207
4
8
Order By: Relevance
“…This study like other studies comparing delirious patients to non-delirious controls found that delirious patients are usually older, sometimes this finding reaches statistical significance as found by van Munster et al [11] and other times not [18]. The cases in this study were significantly older (72.4 ± 9.4) than the controls (66.9 ± 5.3) years.…”
Section: Discussionsupporting
confidence: 84%
“…This study like other studies comparing delirious patients to non-delirious controls found that delirious patients are usually older, sometimes this finding reaches statistical significance as found by van Munster et al [11] and other times not [18]. The cases in this study were significantly older (72.4 ± 9.4) than the controls (66.9 ± 5.3) years.…”
Section: Discussionsupporting
confidence: 84%
“…10 This may be accounted for by the additional delirium risk factors noted in this population. In addition, the peak occurrence of delirium occurred in the second and third weeks posttransplantation.…”
Section: Discussionmentioning
confidence: 92%
“…b Less advanced (LA) disease was defined as acute lymphoblastic leukemia or acute myeloid leukemia in first remission; chronic myeloid leukemia in a chronic phase; or non-Hodgkin lymphoma in first remission, untreated first recurrence, or second remission. More advanced (MA) disease included all other stages of these diseases, all other types of hematologic malignancies, breast carcinoma Ն Stage II, and ovarian carcinoma (see Bensinger et al, 2001 49 10 total body irradiation, 27 and alcohol abuse 23,55,56 all have been implicated in contributing to the occurrence, severity, or duration of delirium or cognitive impairment. Renal and hepatic impairment may be surrogate measures for severe underlying disease and also may impair the metabolism of medications, thus precipitating delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Yu, Park, Hyun, & Lee, 2008). (Chung et al, 2011;Yang, 2010) 을 포함하였고, 생활특성으로는 음주, 흡연, 영양상태, 수면상 태 (Cho, Yoo, Choi, & Kim, 2009;Hwang & Lee, 2010;Kim et al, 2008;Lawlor et al, 2000;Yang, 2010;Yu et al, 2008) 3) 질병 및 수술 관련 특성 질병 관련 특성으로 과거 수술력, 동반질환 여부 (Cho et al, 2009;Chung et al, 2011;Contin et al, 2005;Hwang & Lee, 2010;Kim et al, 2008;Yang, 2010;Yu et al, 2008) (Cho et al, 2009;Chung et al, 2011;Contin et al, 2005;Hwang & Lee, 2010;Jung, Park, & Rim, 2006;Kim et al, 2008;Lawlor et al, 2000;Marcantonio et al, 1998;Yang, 2010;Yu et al, 2008) Table 3과 …”
unclassified